EFFECT OF FEED SUPPLEMENTATION ON MILK YIED IN SELECTED LAMAS FOR MEAT PRODUCTION - Gonzáles D., Rosario (2007)
Twenty pregnant lamas from the IVITA Research Center, Maranganí, Cusco, were selected, and the rump area, thigh volume, body weight and thoracic perimeter were measured. A 2 x 2 factorial design was used, where A = Supplement (a1: with hay; a2: without hay) and B = Biometric measures (b1: high values; b 2: low values). The amount of supplemented hay was 1 kg/animal/day. The effect of biometric measures and feed supplementation on dam milk production and calf growth during the first seven weeks of lactation was evaluated. Body weight of both dams and calves was weekly recorded. Milk production was estimated (milking after 12 hours of wearing an udder protector to avoid suckling). Supplemented lamas showed higher milk yield (0.05>p<0.01) between the3rd and 7th week of lactation. The peak of milk production occurred at the 2nd (a2) and 3rd (a1) week. Calves of supplemented lamas and those with higher biometric measures had the highest body weight gain (p<0.05). No significant interaction was found between treated groups on calf weight; however, there was a higher growth rate in calves of supplemented lamas with high biometric measures. Correlations between milk yield with calf body weight due to the effect of feed supplementation and biometric measures were significant from the 4th week onwards. The effect of feed supplementation and biometric measures, and the interaction between them did no significantly affect dams body weight during the first weeks of lactation, however, there was a slight reduction of body weight between the 1st and the 3rd week of lactation. The average body weight at parturition and on the 7th week of lactation was 96.9 ± 8.4 and 95.3 ± 9.1 kg respectively. The results showed a significant effect of feed supplementation and biometric measures on milk production and calf body weight.